PTEN Reduces BMP9-Induced Osteogenic Differentiation Through Inhibiting Wnt10b in Mesenchymal Stem Cells - Li, Fu-Shu; Li, Pei-Pei; Li, Ling; Deng, Yan; Hu, Ying; He, Bai-Cheng (Frontiers in Cell and Developmental Biology, 2021)
Bone morphogenetic protein 9 (BMP9) is one of the most efficacious osteogenic cytokines. PTEN and Wnt10b were both implicated in regulating the osteogenic potential of BMP9, but the potential relationship between them keeps unclear. In this study, we determined whether PTEN could affect the expression of Wnt10b in the osteogenic process initialized by BMP9 in mesenchymal stem cells (MSCs), as well as the possible molecular mechanism. We found that PTEN was inhibited by BMP9 in MSCs, but Wnt10b was up-regulated simultaneously. The BMP9-induced osteogenic markers were reduced by PTEN, but increased by silencing PTEN. The effects of silencing PTEN on elevating BMP9-induced osteogenic markers were almost abolished by silencing Wnt10b. On the contrary, the BMP9-induced ALP activities and mineralization were inhibited by PTEN, but almost reversed by the combination of Wnt10b. Ectopic bone formation induced by BMP9 was enhanced by silencing PTEN, which was reduced by silencing Wnt10b. The effect of BMP9 on up-regulating Wnt10b was decreased by PTEN, but enhanced by silencing PTEN. Meanwhile, the effect of BMP9 on inducing Wnt10b was also reduced by PI3K specific inhibitor (Ly294002) or rapamycin, respectively. The BMP9-induced phosphorylation of CREB or Smad1/5/9 were both reduced by PTEN, but enhanced by silencing PTEN. In addition, p-CREB interacts with p-Smad1/5/9 in MSCs, and p-CREB or p-Smad1/5/9 were enriched at the promoter region of Wnt10b. Our findings indicated that inhibitory effects of PTEN on the osteogenic potential of BMP9 may be partially mediated through decreasing the expression of Wnt10b via the disturbance of interaction between CREB and BMP/Smad signaling.